Reliability analysis of the Reykjavik Area Control Center Air Traffic Management system - Unnur Þórleifsdóttir 1985- (2013)
In a world of continuous growth in the demand for air transport services it has become increasingly important to develop new methods for evaluating risk and safety in civil aviation. Air Traffic Management (ATM) systems represent essential infrastructure that is critical to flight safety. In extreme cases failure of the ATM system can result in loss of life. Consequently it is of utmost importance to make all possible efforts to improve the reliability of the ATM and connected systems by minimizing the probability of failures. Isavia is the Icelandic Air Navigation Service Provider responsible for providing air navigation services in one of the largest Air Traffic Control regions in the world (5.4 million square kilometers in the North Atlantic). The ability to provide safe and efficient air navigation services is highly dependent on the ATM system located in the Reykjavík Air Traffic Control Center (RACC). The main focus of this research project is on developing a reliability model that can be used to ascertain the risk of technical failure in the ATM system of the RACC ATM system. The Failure Mode Effect and Criticality Analysis (FMECA) and Reliability Block Diagram (RBD) are employed along with a software tool, BlockSim, in order to develop a quantitative model that is used to determine the effect of RACC electrical power system failures on the reliability of the ATM system. This approach is a first attempt at evaluating the overall reliability of the RACC ATM system. The main conclusion of this work is that the approach and the methods employed are very attractive for evaluating reliability of the RACC ATM system and similar systems. The reliability of the ATM system is computed to determine the effect of electrical failures in various modes of operation. As an example it is found that the Mean Time to Failure is about 4.3 years in a typical operational mode. Also improvements in reliability are considered e.g. by increasing system redundancy. This revealed that adding a fuse board to the electrical power ...